Micro-hole array fluorescent sensor based on AC-Dielectrophoresis (DEP) for simultaneous analysis of nano-molecules - Kim, Hye Jin; Kang, Dong-Hoon; Lee, Eunji; Hwang, Kyo Seon; Shin, Hyun-Joon; Kim, Jinsik; Park, Jung Ho (ADVANCED BIOMEDICAL AND CLINICAL DIAGNOSTIC AND SURGICAL GUIDANCE SYSTEMS XVI, 2018)
We propose a simple fluorescent bio-chip based on two types of alternative current-dielectrophoretic (AC-DEP) force, attractive (positive DEP) and repulsive (negative DEP) force, for simultaneous nano-molecules analysis. Various radius of micro-holes on the bio-chip are designed to apply the different AC-DEP forces, and the nano-molecules are concentrated inside the micro-hole arrays according to the intensity of the DEP force. The bio-chip was fabricated by Micro Electro Mechanical system (MEMS) technique, and was composed of two layers; a SiO2 layer and Ta/Pt layer were accomplished for an insulation layer and a top electrode with micro-hole arrays to apply electric fields for DEP force, respectively. Each SiO2 and Ta/Pt layers were deposited by thermal oxidation and sputtering, and micro-hole arrays were fabricated with Inductively Coupled Plasma (ICP) etching process. For generation of each positive and negative DEP at micro-holes, we applied two types of sine-wave AC voltage with different frequency range alternately. The intensity of the DEP force was controlled by the radius of the micro-hole and size of nano-molecule, and calculated with COMSOL multi-physics. Three types of nano-molecules labelled with different fluorescent dye were used and the intensity of nano-molecules was examined by the fluorescent optical analysis after applying the DEP force. By analyzing the fluorescent intensities of the nano-molecules, we verify the various nano-molecules in analyte are located successfully inside corresponding micro-holes with different radius according to their size.